A New Stepwise Molecular Work-Up After Chorionic Villi Sampling in Women With an Early Pregnancy Loss - Pauta, Montse; Badenas, Cèlia; Rodriguez-Revenga, Laia; Soler, Anna; Grande, Maribel; Sabrià, Joan; Illanes, Carmen; Borobio, Virginia; Borrell, Antoni (Frontiers in Genetics, 2021)
OBJECTIVE: To Explore the use of a new molecular work-up based on the stepwise use of Quantitative Fluorescence Polymerase Chain Reaction (QF-PCR) extended to 8 chromosomes and single nucleotide polymorphism array (SNP-array) in chorionic villi obtained by chorionic villi sampling (CVS) offered to women experiencing an early pregnancy loss. METHODS: During a 3-year period (January 2016-December 2018), CVS was offered to women experiencing an early pregnancy loss before the evacuation of the products of conception (POC) to retrieve chorionic villi, irrespectively of the number of previous losses. A new molecular work-up was prospectively assayed encompassing a first QF-PCR round (with the 21, 18, 13, 7, X and Y chromosomes), a second QF-PCR round (with the 15, 16 and 22 chromosomes), and a high resolution SNP-array in those cases with normal QF-PCR results. A control group in which POC were collected after surgical uterine evacuation was used to be compared with the intervention group. RESULTS: 459 women were enrolled in the intervention group (CVS) and 185 in the control group (POC after uterine evacuation). The QF-PCR testing success rates were significantly higher in the intervention group (98.5%: 452/459) as compared to the control group (74%: 109/147) (p<0.001), while the chromosomal anomaly rate at the 2 QF-PCR rounds was similar between the two groups: 52% (234/452) in the intervention and 42% (46/109) in the control group (p=0.073). SNP-array was performed in 202 QF-PCR normal samples of the intervention group and revealed 67 (33%) atypical chromosomal anomalies (>10 Mb), 5 (2.5%) submicroscopic pathogenic copy number variants and 2 (1%) VOUS. CONCLUSION: Eighty-two percent of women experiencing an early pregnancy loss opted for a CVS. The testing success rates were higher in the intervention group (CVS) (98%) as compared to the control group (POC) (74%). The overall yields were 52% by QF-PCR (including 3 complete hydatiform moles), and 16% by SNP-array including 15% atypical chromosomal anomalies and 1.1% submicroscopic pathogenic copy number variants.